Postprocessing of Infrared Reflectography to Support the Study of a Painting: The Case of Vivarini's Polyptych - Laura Fragasso; Nicola Masini (International Journal of Geophysics)
Infrared (IR) reflectography is an imaging diagnostic technique widely used to study and evaluate the assessment of paintings' conservation state. The study case analyzed in this paper is related to a polyptych panel attributed to Vivarini's workshop conserved in the “Sigismondo Castromediano” Museum in Lecce. The painting's IR reflectography has been acquired through a CCD camera with spectral sensitivity ranging 400–1150 nm and manual positioning system. In order to offset the technological limits of the CCD camera, reflectograms have been processed through Principal Component Analysis and spectral indices. Postprocessing provided information related to the different pictorial drafting and restoration works, as well as emphasized graphic details and shadings, useful to improve the knowledge of the painting techniques.